Increased Expression of FGF‐21 Negatively Affects Bone Homeostasis in Dystrophin/Utrophin Double Knockout Mice. (30th December 2019) - Li, Hongshuai; Sun, Hui; Qian, Baoli; Feng, Wei; Carney, Dwayne; Miller, Jennifer; Hogan, MaCalus V; Wang, Ling
ABSTRACT: Duchenne muscular dystrophy (DMD) is the most common muscular dystrophy seen in children. In addition to skeletal muscle, DMD also has a significant impact on bone. The pathogenesis of bone abnormalities in DMD is still unknown. Recently, we have identified a novel bone‐regulating cytokine, fibroblast growth factor‐21 (FGF‐21), which is dramatically upregulated in skeletal muscles from DMD animal models. We hypothesize that muscle‐derived FGF‐21 negatively affects bone homeostasis in DMD. Dystrophin/utrophin double‐knockout (dKO) mice were used in this study. We found that the levels of circulating FGF‐21 were significantly higher in dKO mice than in age‐matched WT controls. Further tests on FGF‐21 expressing tissues revealed that both FGF‐21 mRNA and protein expression were dramatically upregulated in dystrophic skeletal muscles, whereas FGF‐21 mRNA expression was downregulated in liver and white adipose tissue (WAT) compared to WT controls. Neutralization of circulating FGF‐21 by i.p. injection of anti‐FGF‐21 antibody significantly alleviated progressive bone loss in weight‐bearing (vertebra, femur, and tibia) and non–weight bearing bones (parietal bones) in dKO mice. We also found that FGF‐21 directly promoted RANKL‐induced osteoclastogenesis from bone marrow macrophages (BMMs), as well as promoted adipogenesis while concomitantly inhibiting osteogenesis of bone marrow mesenchymal stem cells (BMMSCs). Furthermore, fibroblast growth factor receptors (FGFRs) and co‐receptor β‐klotho (KLB) were expressed in bone cells (BMM‐derived osteoclasts and BMMSCs) and bone tissues. KLB knockdown by small interfering RNAs (siRNAs) significantly inhibited the effects of FGF21 on osteoclast formation of BMMs and on adipogenic differentiation of BMMSCs, indicating that FGF‐21 may directly affect dystrophic bone via the FGFRs‐β‐klotho complex. In conclusion, this study shows that dystrophic skeletal muscles express and secrete significant levels of FGF‐21, which negatively regulates bone homeostasis and represents an important pathological factor for the development of bone abnormalities in DMD. The current study highlights the importance of muscle/bone cross‐talk via muscle‐derived factors (myokines) in the pathogenesis of bone abnormalities in DMD. © 2019 American Society for Bone and Mineral Research.